Word Cloud Analysis and Business Model of Science Techno Park in Indonesian Universities - Sasongko, Agung Hari; Syarief, Rizal; Rochman, Nurul Taufiqu; Amanah, Siti (Sekolah Tinggi Manajemen IPMI, 2025)
The government issued a presidential regulation on national entrepreneurship development to strengthen the economic structure, and the government will add 1 million entrepreneurs. Universities play an essential role but must involve the industry and create a conducive environment. Science Techno Park unites the sector and academia by providing an environment that fosters interaction. Presidential Regulation No. 18 of 2020 mandates the establishment of Science Techno Parks based on higher education institutions. We studied the future of science and technology parks in Indonesia by analyzing news articles from websites between 2019 and 2024. The results of the word cloud analysis showed that the word